Osteoarthritis: insights into pathogenesis and futuristic treatment strategies - Singh, Ajay; Rai, Vikramaditya; Pandey, Sushmita; Chavan, Manisha; Ketha, Deepthi (International Journal of Research in Orthopaedics, 2022)
Osteoarthritis is the most common musculoskeletal condition world over that causes significant health, economic, and societal burdens. Till date, no therapeutic approaches have been able to stop or delay the progression of osteoarthritis satisfactorily. Structural and clinical features of the disease are characterized by a high inter-patient variability. This heterogeneity is believed to be a major factor associated with the complexity of osteoarthritis and the on-going difficulty to identify a single therapy for all sub-groups. The objective of this review is to highlight recent advances in the understanding of the pathophysiology of osteoarthritis and latest biological treatments available, their limitations and to bring to notice the latest state-of-the-art on-going research on novel therapies. For this study we searched different online databases such as PubMed and Cochrane Library from inception to January 2022. We identified eligible studies on the pathophysiologic findings, prevalence, or incidence of knee osteoarthritis, available treatments, and current research for future therapies. Besides the availability of vast literature on cartilage extracellular matrix and its changes in osteoarthritis, the complicated mechanism of the disease still has missing links in the chain. Presently, biological treatments such as platelet rich plasma, bone marrow mesenchymal stem cells and autologous fragmented adipose tissue containing structural vascular fraction are commonly used. In future, gene therapy could become a potential option for treating the disease. More extensive insights into the pathophysiology of osteoarthritis will be helpful in designing therapies that can curb structural progression and promote cartilage regeneration thus providing more potent relief from painful and disabling condition associated with osteoarthritis.